Changes in isovitexin-O-glycosylation during the development of young barley plants. (April 2018) - Brauch, Dominic; Porzel, Andrea; Schumann, Erika; Pillen, Klaus; Mock, Hans-Peter
Abstract: Phenylpropanoids are a class of plant natural products that have many biological functions, including stress defence. In barley, phenylpropanoids have been described as having protective properties against excess UV-B radiation and have been linked to resistance to pathogens. Although the phenylpropanoid composition of barley has recently been addressed in more detail, the biosynthesis and regulation of this pathway have not been fully established. Barley introgression lines, such as the S42IL-population offer a set of genetically diverse plants that enable the correlation of metabolic data to distinct genetic regions on the barley genome and, subsequently, identification of relevant genes. The phenylpropanoid profiles of the first and third leaf of barley seedlings in Scarlett and four members of the S42IL-population were obtained by LC-MS. Comparison of the leaf profiles revealed a change in the glycosylation pattern of the flavone-6- C -glucoside isovitexin in the elite cultivar Scarlett . The change was characterized by the stepwise decrease in isovitexin-7- O -glucoside (saponarin) and an increase in isovitexin-2″- O -β-D-glucoside content. The lines S42IL-101-, -177 and -178 were completely devoid of isovitexin-2″- O -β-D-glucoside. Parallel glucosyltransferase assays were consistent with the observed metabolic patterns. The genetic region responsible for this metabolic effect was located on chromosome 1H between 0.21 and 15.08 cM, encompassing 505 gene candidates in the genome of the sequenced cultivar Morex . Only one of these genes displayed sequence similarity with glucosyltransferases of plant secondary metabolism that possessed the characteristic PSPG motif. Graphical abstract: Highlights: Barley showed a changed isovitexin- O -glycosylation profile during plant development. Four members of S42IL-population had an alternating phenolic profile. An increase of a 2″UGT activity during plant development is indicated. HORVUHr1G002710.1 is a candidate gene for a 2″UGT. HORVUHr1G002710.1 showed sequence similarities to secondary compound UGTs.